2018
DOI: 10.1016/j.cels.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Gain of CTCF-Anchored Chromatin Loops Marks the Exit from Naive Pluripotency

Abstract: SummaryThe genome of pluripotent stem cells adopts a unique three-dimensional architecture featuring weakly condensed heterochromatin and large nucleosome-free regions. Yet, it is unknown whether structural loops and contact domains display characteristics that distinguish embryonic stem cells (ESCs) from differentiated cell types. We used genome-wide chromosome conformation capture and super-resolution imaging to determine nuclear organization in mouse ESC and neural stem cell (NSC) derivatives. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 80 publications
3
61
0
Order By: Relevance
“…Although previous studies have demonstrated a global reduction in chromatin accessibility and/or plasticity during lineage commitment in specific developmental settings (e.g. embryonic stem cells, intestinal stem cells, and neural stem cells 35,36,38,64 ), our quantitative findings extend the scope of this result. Moreover, as has been previously shown 65 , our data indicate that variability in gene counts between phenotypically identical single cells is not exclusively due to drop-out events, but also due to differential sampling of the transcriptome (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although previous studies have demonstrated a global reduction in chromatin accessibility and/or plasticity during lineage commitment in specific developmental settings (e.g. embryonic stem cells, intestinal stem cells, and neural stem cells 35,36,38,64 ), our quantitative findings extend the scope of this result. Moreover, as has been previously shown 65 , our data indicate that variability in gene counts between phenotypically identical single cells is not exclusively due to drop-out events, but also due to differential sampling of the transcriptome (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Since the transcriptional output of a cell is associated with its genome-wide chromatin profile, we hypothesized that single-cell gene counts might ultimately be a surrogate for global chromatin accessibility, which has been previously shown to decrease with differentiation [35][36][37][38] . To test this, we compared single-cell gene counts derived from scRNA-seq data with paired bulk ATAC-seq (assay for transposase-accessible chromatin sequencing) profiles obtained from a recent study of in vitro mesodermal differentiation from human embryonic stem cells (hESCs) 32 ( Fig.…”
Section: Robustness and Biological Basis Of Gene Countsmentioning
confidence: 99%
“…Although almost all TAD boundaries are enriched by CTCF and cohesin, the majority of CTCFbound sites are found elsewhere in the genome (Merkenschlager and Nora, 2016). Furthermore, CTCF and cohesin binding sites are significantly conserved among cell types, but still many of them, as well as many TADs, display cell-type specific patterns and changes during differentiation as a result of stage-specific transcription factors (Pekowska et al, 2018;Stadhouders et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between sub-chromosomal domains form two major types of spatial compartments referred to as A and B (Lieberman-Aiden et al, 2009;Rao et al, 2014) and chromatin contacts are more frequent between regions within the same compartment type (Imakaev et al, 2012;Pombo and Dillon, 2015). Further partitioning of the genome creates megabase-scale topologically associating domains (TADs) that are largely invariant across cell types, and smaller, nested sub-TADs, chromatin loops and insulating neighbourhoods that are frequently reorganised between cellular states (Bonev et al, 2017;Dixon et al, 2012;Dowen et al, 2014;Nora et al, 2012;Pękowska et al, 2018;Phillips-Cremins et al, 2013;Rao et al, 2014;Sanyal et al, 2012;Sexton et al, 2012;Stadhouders et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These events recapitulate similar molecular transitions as embryos progress from pre-to post-implantation stages of development (Auclair et al, 2014;Borgel et al, 2010;Liu et al, 2016;Smith et al, 2012) and PSCs therefore provide a tractable cell model to investigate these processes. In mouse PSCs, global epigenetic changes occur in parallel with the reorganisation of gene regulatory interactions that take place within largely preserved structural domains (Beagan et al, 2017;Pękowska et al, 2018). For example, the acquisition of H3K27me3 at gene promoters during the transition from a naïve to a primed state is concomitant with the emergence of a long-range network of promoter-promoter interactions that connect the H3K27me3 marked regions (Joshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%